Auditory Function following Post-dural Puncture Headache Treated with Epidural Blood Patch: A Long-term Follow-up. Issue 2 (June 2016) - Darvish, B.; Dahlgren, G.; Irestedt, L.; Magnuson, A.; Möller, C.; Gupta, A.
Abstract : ( Acta Anaesthesiologica Scandinavica . 59 (2015) 1340–1354) Epidural analgesia is commonly used to manage pain during labor, and in roughly 1% of cases an accidental dural puncture (ADP) results. When ADP occurs, patients frequently experience a severe post-dural puncture headache (PDPH) and can also suffer transient hearing loss. One of the methods used to treat PDPH is an epidural blood patch (EBP). The short- and long-term effects that ADP and this treatment have on auditory function are not known, but the authors of this study hypothesized that there could be residual hearing loss. The study examined the long-term changes in auditory function for patients who suffered ADP and were treated with an EBP. The data for the study were collected from a group of sixty Swedish women, without documented hearing problems, who had experienced an ADP during labor and were treated with an EBP between 2005 and 2011. These women were tested in 2013 for hearing function and given a questionnaire on perceived hearing impairments. The control group consisted of twenty healthy, non-pregnant women of similar age who had not received a neuraxial block during their previous pregnancies. Each subject answered a general health and a specific hearing questionnaire. Otoscopy examination and pure tone and speech audiometry tests were performed on patients in both the study and control groups. Hearing levels were summarized by the mean and standard deviation using a 3-way analysis of variance model.